Perceived Communication Challenges of Tourist Guides: A Study on Local Tourist Guides at Tetebatu Tourism Village - Alfathya, Roro Ranti Dea; Amin, Muhammad; Wardana, Lalu Ali (LITPAM, 2026)
Effective communication between local tour guides and foreign tourists is essential for the success of community-based tourism, yet many local guides in Indonesia face significant linguistic barriers that hinder their ability to deliver informative and engaging tours. This study aims to identify the communication challenges faced by local tour guides in Tetebatu Tourism Village and the strategies they employ to overcome these challenges. This study employs a qualitative descriptive design with three local tour guides as participants, selected through purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and document analysis. The findings indicate that tour guides face two categories of challenges: (1) language-based challenges, including forgetting vocabulary, the influence of the Sasak accent, pauses in speech, and grammatical limitations, and (2) content-based challenges, such as explaining religious topics, local culture, and historical narratives. To overcome these challenges, they employ nonverbal strategies such as pointing at objects, hand gestures, showing photos or videos on their cell phones, maintaining eye contact and smiling, as well as confirmation strategies by directly asking tourists whether they understand. This study concludes that Tetebatu tour guides face significant communication challenges but have developed various strategies to overcome them. The findings have important implications for the development of more targeted English language training programs for local tour guides, particularly in the areas of vocabulary enrichment, pronunciation practice, and cultural communication skills. Furthermore, the results suggest that tourism stakeholders and local governments should invest in sustainable training initiatives that address both linguistic competence and strategic communication skills to enhance the quality of tourism services and support the long-term sustainability of community-based tourism in Tetebatu.